Micro extrusion of innovative alumina pastes based on aqueous solvent and eco-friendly binder. Issue 7 (July 2018) - Bourret, J.; El Younsi, I.; Bienia, M.; Smith, A.; Geffroy, P.-M.; Marie, J.; Ono, Y.; Chartier, T.; Pateloup, V.
Abstract: The aim of this work is to develop the micro-extrusion process with an innovative approach linked to respect for the principles of green chemistry. Alumina pastes are prepared in an aqueous medium with psyllium as a natural binder, which is not derived from the petrochemical industry. The challenge is to obtain a concentrated system which is suitable for the micro-extrusion process and which ensures satisfactory structural and mechanical properties of the final parts. The manufacturing of alumina networks is achieved by using the micro-extrusion shaping process consisting of an XYZ displacement platform and a homemade extrusion head. The nozzle diameter is equal to 400 μm. The rheological behavior of the paste is studied as well as its capability to be extruded. The green parts are consolidated by heat treatment at 1600 °C. Their microstructural characteristics have been studied. Final density equal to 98% has been obtained.